Corporate social responsibility, country-level predispositions, and the consequences of choosing a level of disclosure. Issue 2 (23rd February 2016) - de Villiers, Charl; Marques, Ana
Abstract : We study the different levels of corporate social responsibility (CSR) disclosures of the largest European firms. We find that firms are more predisposed to disclose more CSR information in countries with better investor protection, higher levels of democracy, more effective government services, higher quality regulations, more press freedom, and a lower commitment to environmental policies. Our analysis of the association of different levels of CSR disclosure with share prices indicates that a high level of CSR disclosure is associated with higher share prices, whereas a low level of CSR disclosure in sensitive industries is associated with lower share prices (compared to no disclosure). These results are also present when we analyse changes in CSR disclosure and are robust to the inclusion of an accounting quality measure in our model. The overall effect of the association of higher levels of CSR disclosure with higher share prices is stronger in countries with more democracy, more government effectiveness, better regulatory quality, and more press freedom. Therefore, market participants find CSR disclosures more informative in countries where investors are in a better position to voice their concerns and where there is better regulation and more effective government implementation of regulations.